Association between variants in nicotinic acetylcholine receptor genes and smoking cessation in a Chinese rural population. Issue 4 (19th May 2016) - Wang, Qiang; Li, Suyun; Pan, Lulu; Li, Huijie; Yang, Xiaorong; Jiang, Fan; Zhang, Nan; Han, Mingkui; Jia, Chongqi
Abstract : Background and Objectives: Genetic studies have revealed a significant association between variants in nicotinic acetylcholine receptor (CHRN) genes and smoking cessation, but the results are inconsistent. In this study, we aimed to examine the relationship between single nucleotide polymorphisms (SNPs) in seven CHRN genes and smoking cessation in a Chinese rural population. Methods: Participants were recruited from 17 villages of 3 counties in Shandong, China. DNA was extracted from the blood samples. Thirty‐two SNPs in seven CHRN genes were genotyped. Logistic regression was used to explore the relationship between single SNP and smoking cessation. Pearson's χ 2 test was performed to test the association between haplotype and smoking cessation. Results: Rs578776 (in CHRNA3), rs660652 (in CHRNA3), and rs588765 (in CHRNA5) were significantly related to smoking cessation. Two haplotypes were associated with smoking cessation. Conclusions: This study confirmed the association between CHRN genes and smoking cessation in the Chinese rural population. Scientific Significance: Our findings provide confirmatory support to the role of CHRN genes to the etiology of smoking cessation in the Chinese rural population. (Am J Addict 2016;25:297–300)